2011
DOI: 10.1189/jlb.1210708
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous PMN sialidase activity exposes activation epitope on CD11b/CD18 which enhances its binding interaction with ICAM-1

Abstract: Diapedesis is a dynamic, highly regulated process by which leukocytes are recruited to inflammatory sites. We reported previously that removal of sialyl residues from PMNs enables these cells to become more adherent to EC monolayers and that sialidase activity within intracellular compartments of resting PMNs translocates to the plasma membrane following activation. We did not identify which surface adhesion molecules were targeted by endogenous sialidase. Upon activation, β2 integrin (CD11b/CD18) on the PMN s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 32 publications
5
74
0
Order By: Relevance
“…However, the sialyl linkages from each anatomic section of the airway are species specific. Using lectin blot techniques established in our laboratory (33), we determined the sialylation status of murine lung tissues and their response to sialidase treatment. Lectins are a group of proteins that bind specifically to different glycoconjugates: SNA and MAA II recognize terminal sialic acids in α-2,6- or α-2,3-linkages, respectively, while PNA recognizes a subterminal β-galactose after terminal sialyl residues have been removed (33, 34).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the sialyl linkages from each anatomic section of the airway are species specific. Using lectin blot techniques established in our laboratory (33), we determined the sialylation status of murine lung tissues and their response to sialidase treatment. Lectins are a group of proteins that bind specifically to different glycoconjugates: SNA and MAA II recognize terminal sialic acids in α-2,6- or α-2,3-linkages, respectively, while PNA recognizes a subterminal β-galactose after terminal sialyl residues have been removed (33, 34).…”
Section: Resultsmentioning
confidence: 99%
“…In a subsequent publication, we demonstrated that removal of sialyl residues from the TLR4 receptor complex accelerated and enhanced LPS-initiated signaling (21). Further, removal of sialyl residues led to activation of PMN β2 integrins and enhanced adhesion, while desialylation of ICAM-1 promoted leukocyte arrest in an in vivo model of cell migration (33). Recently, we reported that MUC1 and the EGF receptor on airway epithelial cells were highly sialylated and that desialylation enhanced their responsiveness to their cognate ligands (52).…”
Section: Discussionmentioning
confidence: 99%
“…VCAM-1 and ICAM-1 binding assays were done as described in previous studies [51]-[53]. Blood was collected from SR-BI +/+ apoE-R61 h/h or SR-BI −/− apoE-R61 h/h mice fed a normal chow diet.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies in vitro and in mouse models have implicated NEU1 in fundamental biological processes that go beyond its canonical degradative function; these include immune response and inflammation [11, 12], cell proliferation [13, 14], and tumor cell migration and metastasis [1, 15, 16]. A primary role of NEU1 as a negative regulator of lysosomal exocytosis has been identified [1720].…”
Section: Introductionmentioning
confidence: 99%